THE EFFECT OF BAGASSE FIBER ADDITION IN FLEXURAL STRENGTH OF BULK FILL COMPOSITE RESIN - Ananda, Siti Farida Rizki; Erlita, Isyana; DH, Irnamanda (Dentino, 2018)
Background: Bulk fill composite resin is a packable composite resin that has been modified to solve the deficiency of conventional composite resin. The addition of fiber can increase the mechanical properties, one of them is flexural strength. Fiber is consisted of two types which are synthetic fiber and natural fiber. In Indonesia, there are many natural fibers, one of them is from the plant of sugarcane. The baggase is the residual from sugarcane plant that had been processed for the making of sugar. Purpose: To acknowledge if the addition of baggase fiber affect the flexural strength of bulk fill composite resin. Methode: This study wastrue experimental studywith post-test only control group design and used simple random sampling that consisted of 3 groups, which are group with addition of baggase fiber, group without addition of baggase fiber as the negative control and group with addition of synthetic fiber as the positive control. Flexural strength tested with Universal Testing Machine. Result: The average value of flexural strength on group with addition of baggase fiber, group without addition of baggase fiber and group with addition of synthetic fiber were 123,549 MPa; 118,125 MPa and 144,442 Mpa respectively. One Way Anova and Post Hoc Bonferroni test showed that there is significant difference between all treatment groups. Conclusion: Based on this study, it can be concluded that addition of baggase fiber can increase the flexural strength but cannot replace the synthetic fiber.